DAMPAK YURIDIS, PSIKOLOGI DAN SOSIOLOGIS BAGI PEREMPUAN DAN ANAK NIKAH SIRRI - Ramoddin; Misbahuddin; Nasaruddin; Suharto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2024)
Currently, Sirri marriage is still often used as an alternative to anticipate free association between non-mahram men and women who are psychologically, morally, and materially not ready to marry formally. So sirri marriage leaves a very complicated problem for the perpetrators, not only legal problems but also psychological and sociological problems concerning the future of children, regarding guardians in marriage and inheritance status. The purpose of this writing is so that we can find out what and how the impact of sirri marriage is. This study uses a qualitative method with a literature study approach in reading and assessing the phenomenon of sirri marriage in society. The data sources in this study come from several books, journals, theses, articles, or scientific papers. The data that has been collected is then analyzed using critical analysis techniques. The results of this study state that unregistered marriage in Islamic law in several conventional fiqh books can be interpreted as a marriage that is hidden because it does not fulfill the pillars and requirements for a valid marriage and is based on the traditions of Arab countries at that time. In the end, an unregistered marriage can be understood as a marriage that has fulfilled the provisions of Islamic law but is not widely announced through a wedding party (walīmah al-‘ursy). The future recommendation of this study is to use quantitative methods to measure the legal, psychological, and sociological impacts on women and children of unregistered marriage